2019
DOI: 10.1155/2019/6436420
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion of Zusanli (ST36) and Shenshu (BL23) Alleviates Cartilage Degradation through RANKL/OPG Signaling in a Rabbit Model of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a systemic and chronic autoimmune inflammatory disease characterized by severe synovial hyperplasia associated with progressive cartilage degradation. Due to the severe pain and disability caused by RA, effective therapeutic strategies that could simultaneously alleviate the inflammatory response and delay the disease progression are urgently needed. As a major alternative therapy in traditional Chinese medicine, moxibustion has been demonstrated that it could reduce the chronic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…ST36 and BL23 are commonly used in acupuncture and moxibustion clinical practice. Animal experiments confirmed that moxibustion of ST36 and BL23 alleviated the cartilage degradation and bone destruction in a rabbit model of RA [15]; electroacupuncture on ST36 and GB39 inhibits synovial angiogenesis in a rat model of adjuvant arthritis [29]. In our study, moxibustion-stimulated ST36, BL23, and Ashi points can improve clinical symptoms, reducing contents of TNF- α , IL-1 β that revealed the analgesic, anti-inflammatory effects in treating RA.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…ST36 and BL23 are commonly used in acupuncture and moxibustion clinical practice. Animal experiments confirmed that moxibustion of ST36 and BL23 alleviated the cartilage degradation and bone destruction in a rabbit model of RA [15]; electroacupuncture on ST36 and GB39 inhibits synovial angiogenesis in a rat model of adjuvant arthritis [29]. In our study, moxibustion-stimulated ST36, BL23, and Ashi points can improve clinical symptoms, reducing contents of TNF- α , IL-1 β that revealed the analgesic, anti-inflammatory effects in treating RA.…”
Section: Discussionsupporting
confidence: 74%
“…Moxibustion is a kind of traditional Chinese therapy, which has the advantage of good clinical efficacy and no toxic effects. A study has shown that moxibustion can regulate inflammatory cytokines and VEGF in RA [14], which can also significantly inhibit the proliferation and secretion of RA synovial cells, thus effectively improving the synovial inflammation hyperemia, edema, and joint cavity effusion and having good anti-inflammatory, analgesic, and immunomodulatory effects [15]. In our previous study, we found the contents of HIF-1 α and VEGF can be regulated by moxibustion ST 36 and BL 23 to inhibit the formation of blood vessels in RA rabbit synovial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous basic researches and clinical studies have shown that moxibustion at ST36, BL23, and Ashi points can significantly improve the clinical symptoms of RA patients, and its mechanism may be related to the regulation of cytokines and signal pathways, such as IL-1 β , TNF- α , HIF-1 α , and NF- kB [ 22 , 23 ]. Besides, some studies have confirmed that moxibustion at ST36 and BL23 could improve synovitis by regulating the RANKL/OPG signaling pathway and IL-17 [ 24 , 25 ]. So, the improvement of clinical symptoms of RA patients by moxibustion may be related to the anti-inflammatory and analgesic effects of moxibustion and the regulation of autoimmunity by acupoints, and moxibustion at ST36, BL23, and Ashi points can regulate a variety of cytokines and signal pathways; its internal mechanism is worthy of further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the previously mentioned analysis and numerous research results indicates that the biological mechanism of moxibustion in the treatment of RA involves several aspects. Researchers have conducted many studies from the perspective of anti-inflammatory, immune regulation, regulation of circadian rhythm, and bone protection [ 41 – 44 ]. Among them, there are studies concentrating on anti-inflammatory effect as the most important aspect because RA is characterized by synovitis, which may result in cartilage and bone destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, there are studies concentrating on anti-inflammatory effect as the most important aspect because RA is characterized by synovitis, which may result in cartilage and bone destruction. Previous studies explored the mechanisms of moxibustion in treating RA from several aspects, including restoring the balance between Th1 and Th2 by regulating the levels of inflammatory cytokines [ 23 , 27 ], modulating the pathological circadian rhythm of TNF- α , IL-1 β , and IL-6 [ 20 , 25 , 31 ], regulating the function of HPAA [ 31 ], alleviating cartilage degradation through RANKL/OPG signaling pathway [ 44 ], and strengthening the negative regulation of PD-1/PD-L1 signaling pathway [ 30 , 32 ]. This study suggested that moxibustion can relieve synovitis of the joint with RA mainly by inhibiting the secretion of proinflammatory cytokines and enhancing the secretion of anti-inflammatory cytokines to restore the equilibrium between Th1 and Th2.…”
Section: Discussionmentioning
confidence: 99%